Fine Mapping and Transcriptome Analysis of Virescent Leaf Gene v-2 in Cucumber (Cucumis sativus L.) - Zhang, Kaijing; Li, Ying; Zhu, Wenwei; Wei, Yifan; Njogu, Martin Kagiki; Lou, Qunfeng; Li, Ji; Chen, Jinfeng (Frontiers in Plant Science, 2020)
Leaf color mutants are the ideal materials to explore the pathways of chlorophyll metabolism, chloroplast development and photosynthesis system. In this study, a new virescent leaf mutant 104Y was identified by spontaneous mutation, whose cotyledon and upper five true leaves were yellow color. The yellow true leaves gradually turned green from top to bottom with increased chlorophyll contents. Genetic analysis indicated that the virescent leaf was controlled by one single recessive gene v-2, which was accurately mapped into 36.0-39.7 Mb interval on chromosome 3 by using BSA-seq and linkage analysis. Fine mapping analysis further narrowed v-2 into 73-kb genomic region including 8 genes with BC1 and F2 populations. Through BSA-seq and cDNA sequencing analysis, only one nonsynonymous mutation existed in the Csa3G890020 gene encoding auxin F-box protein was identified, which was predicted as the candidate gene controlling virescent leaf. Comparative transcriptome analysis and quantitative real-time PCR analysis revealed that the expression level of Csa3G890020 was not changed between EC1 and 104Y. However, RNA-seq analysis identified that the key genes involved in chlorophyll biosynthesis and auxin signaling transduction network were mainly down-regulated in 104Y compared with EC1, which indicated that the regulatory functions of Csa3G890020 could be performed at post-transcriptional level rather than transcriptional level. This is the first repot to map-based clone an auxin F-box protein gene related to virescent leaf in cucumber. The results will exhibit a new insight into the chlorophyll biosynthesis regulated by auxin signaling transduction network.